Microbiological models for accelerated development of secondary caries in vitro. (December 2022) - Ionescu, Andrei C.; Hahnel, Sebastian; Delvecchio, Paolo; Ilie, Nicoleta; Moldovan, Marioara; Zambelli, Vanessa; Bellani, Giacomo; Brambilla, Eugenio
Abstract: Objectives: The current study aimed to compare the efficacy of two in vitro microbiological models based on open and closed systems designed to obtain secondary caries in an accelerated and reproducible way. Methods: A conventional resin-based composite (RBC - Majesty ES-2; Kuraray, Japan) and a resin-modified glass-ionomer cement (RMGIC – Ionolux; VOCO, Germany) were used to restore standardized class II cavities ( n = 4/tooth, cervical margin in dentin) in 16 human molars. The ability to produce secondary caries with S treptococcus mutans biofilms was tested using either an open-cycle or closed-cycle bioreactor ( n = 8 specimens/model). Specimens were scanned before and after the biofilm exposure using micro-CT (Skyscan 1176, 9 µm resolution, 80 kV, 300 mA). Image reconstruction was performed, and demineralization depths (µm) were evaluated at the restoration margins and a distance of 1.0 mm. Results: Dentin demineralization could be observed in all specimens, and enamel demineralization in 50% of the specimens. The open system bioreactor produced lesions with significantly higher overall demineralization depths ( p < .001). However, demineralization depths at a 1.0 mm distance from the restoration margins showed no difference between open and closed systems or materials. In the open system, significantly lower demineralization depths were observed in proximity to RMGIC than RBC ( p < .001), which was not significantly different in the closed system ( p = .382). Conclusions: Both systems produced in vitro secondary caries in an accelerated way. However, the open-cycle bioreactor system confirmed the caries-protective activity exerted by the RMGIC material in contrast to the RBC, better simulating materials' clinical behavior. Clinical significance: The possibility of obtaining accelerated and reproducible secondary caries development in vitro is fundamental in testing the behavior of conventional and yet-to-come restorative dental materials. Such systems can provide faster outcomes regarding the performance of dental restorative materials compared to clinical studies, notwithstanding the importance of the latter.